Thrombotic Thrombocytopenic Purpura: A Paradigm Shift? - Cines, Douglas B.; Konkle, Barbara A.; Furlan, Miha (Thrombosis and Haemostasis, 2000)
The pathophysiology of thrombotic thrombocytopenic purpura (TTP) has fascinated hematologists for decades. What causes seemingly healthy individuals to suddenly develop widespread platelet-rich microthrombi in specific microvascular beds while sparing other vascular sites completely? Is the disorder caused by the sudden appearance of a novel platelet-agglutinating factor or do platelet-rich thrombi form as a consequence of insult to the capillary endothelium? Is the disease self-limiting, does plasma exchange fundamentally alter the pathophysiology of an autoimmune attack on a normal endothelium, or does the immune response develop to microvasculature that has been perturbed and, if so, by what? It has been thought by many of us that the answers to these questions will provide insight into how platelet-vessel wall interactions are normally regulated in the microvasculature and the differences that characterize the behavior of microvascular, arterial and venous systems in various organs. The corollary to these scientific issues is the anticipation that such answers would also lead to new strategies for intervention in other, more common thrombotic diseases.